Help Avoidance: When Students Should Seek Help, and the Consequences of Failing to Do So. Issue 3 (March 2017) - Almeda, Victoria; Baker, Ryan; Corbett, Albert
Background: Across computer-based and traditional classroom settings, recent studies have identified motivational orientation, prior knowledge, self-regulation, and cognitive load as possible factors that affect help-seeking behaviors and their impact on learning. However, the question of whether there is an optimal point for determining when a student needs help has not been fully explored. Purpose of Study: Using data from two modules of the Genetics Cognitive Tutor, the present study investigates this question by examining whether the relationship of help avoidance (failing to seek help when it is needed) and student learning is dependent on the student's level of prior knowledge. We also investigate how the relationship between help avoidance and student learning is mediated by the amount of prior practice, or the number of attempts at a problem step. Research Design: We obtained existing data from the use of the Genetics Cognitive Tutor. We conducted a series of correlational analyses to better understand the relationship between help avoidance and student learning. We correlated students' proportions of help avoidance at different levels of knowledge with measures of robust learning. We also analyzed the relationship between students' proportions of help avoidance and measures of robust learning, taking the amount of practice or the number of attempts at a problem step into account. Results: Our findings suggest that, except at very high or very low knowledge, help avoidance is generally stably (negatively) related to robust learning outcomes. Our results also indicate that help avoidance is more strongly associated with learning outcomes early in the practice sequence, suggesting that students should be encouraged to seek help on problem-solving skills on the first problem, rather than waiting until later problems. Similarly, our results reveal that help avoidance is more negatively associated with learning outcomes on early attempts at a problem step than on later attempts, indicating that students should be encouraged to seek help on the first attempt if help is needed. Conclusions: These findings represent a step toward understanding when students should seek help, with the potential of improving the design of metacognitive support within adaptive learning systems.